Right- and Left-hand Performance on the Rey–Osterrieth Complex Figure: A Preliminary Study in Non-clinical Sample of Right Handed People - Yamashita, H. (Archives of Clinical Neuropsychology, 2010)
Intermanual differences in performing the Rey–Osterrieth Complex Figure Test (ROCFT) were experimentally investigated. Undergraduate participants (n = 120; 60 men, 60 women) were randomly assigned to one of four groups based on the hand used in a copy trial and a recall test. Hand use had a minimal effect on performance in the copy trial. However, recall accuracy was lower when the non-dominant left hand was used in the copy trial than when the dominant right hand was used, regardless of the hand used in the recall test. These findings are important from a clinical perspective, especially in cases in which patients use the non-dominant hand due to hemiplegia of the dominant hand when conducting the ROCFT.